Menakar Nalar Hukum Profetik pada Perilaku Politik Kaum Cendekia: (Konteks Pendekatan Konstruktif Maqashid Syari’ah) - Munir, Arsyul; Munir, Asep Arsyul (Program Studi Hukum Tata Negara, 2024)
The ideals of tranquility, justice, prosperity and constancy of a nation are - at times - compromised by the vested interests of the ruling elite. The manifestation of division is indicated by unstable political behavior. At the grassroots level, fanaticism that usually raises the alibi of freedom of expression is shown through hate speech that knows no empathy. In the name of criticism, sometimes the expression satire is used to legalize more or less the same thought, capitalizing on disagreement. This then takes on the educative role of the general public in justifying irrational political preferences. From here, at least two problems can arise that need to be defined in depth, namely: First, how is the correlation between legal reasoning, religious profetization, and the maqashid shari'ah approach at the individual level [?]; Second, how does the maqashid shari'ah construct measure prophetic legal reasoning in the political behavior of scholars [?] This research is qualitative in nature using bibliometric analysis. The bibliometric approach was originally used in quantitative analysis of scientific literature and publications to understand trends, patterns, and characteristics in a particular field of research. The analysis proposed then rests on the pragamatic value it generates; to the extent that it - in the broader category of the life of the nation and state - bursts out a myriad of positive benefits towards continuous improvement (islah yang ihsan), then to that extent also the effects of its omissions must be tolerated efficiently and effectively. Vice versa. Keywords: Legal Reasoning, Political Behavior, Maqashid Shari'ah